2019
DOI: 10.7717/peerj.6263
|View full text |Cite
|
Sign up to set email alerts
|

Variation in wild pea (Pisum sativumsubsp.elatius) seed dormancy and its relationship to the environment and seed coat traits

Abstract: BackgroundSeed germination is one of the earliest key events in the plant life cycle. The timing of transition from seed to seedling is an important developmental stage determining the survival of individuals that influences the status of populations and species. Because of wide geographical distribution and occurrence in diverse habitats, wild pea (Pisum sativum subsp. elatius) offers an excellent model to study physical type of seed dormancy in an ecological context. This study addresses the gap in knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 112 publications
(175 reference statements)
11
67
0
Order By: Relevance
“…Despite environmental distance not being responsible for wild pea population structure, seed dormancy studies have shown phenotypic variation correlated with environmental conditions, including rainfall patterns (Hradilová et al, 2019). As in other native Mediterranean plants and legume species with physical dormancy barriers, seeds germinate mostly in autumn, after experiencing a hot and dry summer season.…”
Section: Peamentioning
confidence: 99%
“…Despite environmental distance not being responsible for wild pea population structure, seed dormancy studies have shown phenotypic variation correlated with environmental conditions, including rainfall patterns (Hradilová et al, 2019). As in other native Mediterranean plants and legume species with physical dormancy barriers, seeds germinate mostly in autumn, after experiencing a hot and dry summer season.…”
Section: Peamentioning
confidence: 99%
“…Maxent (version 279 3.4.1, Phillips et al, 2018) at default conditions, a maximumentropy based machine learning method was used for modeling purposes. Maxent showed better performance than other methods when samples sizes are small (Hernandez et al, 2006) and it estimates the potential niche instead of the realized distribution of the modeled entity (Phillips et al, 2006;Hradilová et al, 2019). As environmental predictors, bioclimatic and soil variables at a resolution of 2.5 arc minutes were used.…”
Section: Niche Analysismentioning
confidence: 99%
“…PY is a highly heritable trait (Hudson et al, 2015) thus it could be useful germplasm for both breeding and artificial (or natural) selection for higher or lower levels of dormancy (Lacerda et al, 2007). It is probable that observed differences between accessions could be explained by genetic adaptations of HV to the local environment (Baskin and Baskin, 2014) as shown in pea (Hradilová et al, 2019) or by selection for improved genotypes (Fuller and Allaby, 2009;Kluyver et al, 2013;Renzi et al, 2016).…”
Section: Phenotypic Variabilitymentioning
confidence: 99%
“…Three different kinds of dormancy have been described to allow optimal germination timing under specific environmental conditions [8,9]: (1) morphological dormancy (MD) refers to seeds that have an underdeveloped embryo and require time to grow; (2) physiological dormancy (PD) prevents embryo growth and seed germination until chemical changes occur, involving abscisic acid and gibberellins metabolism, among other factors; and (3) physical dormancy (PY) is caused by water-impermeable palisade cells in the seed coat. PY occurs in at least 18 Angiosperm families and is frequent in legumes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, less is known about the factors which release the PY dormancy. Through experimental studies, it was shown that, in addition to scarification, wet or dry heat were found to be effective [8,10,19]. In addition, natural conditions, such as temperature and soil moisture oscillations, are the major players [20,21].…”
Section: Introductionmentioning
confidence: 99%